7 T Musculoskeletal MRI: Fundamentals and Clinical Implementation. Issue 1 (28th January 2023) - Pazahr, Shila; Nanz, Daniel; Sutter, Reto
Abstract: This review summarizes the current state-of-the-art of musculoskeletal 7 T magnetic resonance imaging (MRI), the associated technological challenges, and gives an overview of current and future clinical applications of 1 H-based 7 T MRI. The higher signal-to-noise ratio at 7 T is predominantly used for increased spatial resolution and thus the visualization of anatomical details or subtle lesions rather than to accelerate the sequences. For musculoskeletal MRI, turbo spin echo pulse sequences are particularly useful, but with altered relaxation times, B1 inhomogeneity, and increased artifacts at 7 T; specific absorption rate limitation issues quickly arise for turbo spin echo pulse sequences. The development of dedicated pulse sequence techniques in the last 2 decades and the increasing availability of specialized coils now facilitate several clinical musculoskeletal applications. 7 T MRI is performed in vivo in a wide range of applications for the knee joint and other anatomical areas, such as ultra-high-resolution nerve imaging or bone trabecular microarchitecture imaging. So far, however, it has not been shown systematically whether the higher field strength compared with the established 3 T MRI systems translates into clinical advantages, such as an early-stage identification of tissue damage allowing for preventive therapy or an influence on treatment decisions and patient outcome. At the moment, results tend to suggest that 7 T MRI will be reserved for answering specific, targeted musculoskeletal questions rather than for a broad application, as is the case for 3 T MRI. Future data regarding the implementation of clinical use cases are expected to clarify if 7 T musculoskeletal MRI applications with higher diagnostic accuracy result in patient benefits compared with MRI at lower field strengths.